The democratization of public school: old and new school management models - Maria José Ferreira Ruiz; Edwylson de Lima Marinheiro (Universidade Federal de Santa Maria, 2015)
The objective of this paper is to discuss the changes in the public management models and the implications for educational management.  We assumed that the standard of management of public institutions changes as the restructuring of capitalism and its constant crises. The study makes reference to three management models, namely: bureaucratic management, democratic management and the business management. Concludesthat in public administration there is a predominance of model management business management and bureaucratic management, which has not yet been surpass. However, contradictorily, the democratic management is present in the educational legislation,  due to the struggle of workers in this area, but unfolds very thin and embryonic form in the public schools.